The effect of pasture vegetation on marl formations in the Ilam city limits - shamsallah Asgari; Hamidreza peravan; samad Shadfar; Mashallahe Mohamadpoor; Manouchehr Tahmasebi (تحقیقات کاربردی علوم جغرافیایی)
In some areas, it is surprisingly possible to see a dense cover of rangeland species that has sustained soils and controlled the sedimentation rate of marl lands. It seems that some of the physical and chemical properties of marl are the main reasons for such a cover in the areas covered by Marlene formations. This research was carried out with the aim of thorough and systematic examination of plant species and determining the need for habitat and their protective role in the eastern, southern and western regions of Ilam. For this purpose, 48 specimens of Marne deposit were harvested from three areas and 33 physical and chemical tests were carried out. Botanical investigations were carried out using recurrent field observations and plots at 180 points, and plant specimens were identified after transfer to the plant museum According to the results of experiments on marl samples in these three regions, according to the stratigraphy of marl formations Gurpi, Pabdeh, Gachsaran and Aghajari, the sediments of these three areas were evaluated for the salinity (EC), bulk density (BD), sodium (Na +) and Soil saturation percentage (SP) and some physical parameters such as sand, sand and silt particles have significant differences. This difference can be one of the factors affecting the diversity and diversity of vegetation grown in three areas. The most important point is that in both eastern and western regions of Ilam, the species of Quercus brantii is abundant and dominant, and it can undoubtedly be considered as the most adapted plant species in the areas covered by Marlene formations of Gurpi and Pabdeh in these zones. . The second dominant species is No mu, Ha sa and Zi nu, which is compatible with the southern marl zone of the city of Ilam.